Developing green infrastructure 'thinking': devising and applying an interactive group-based methodology for practitioners. Issue 5 (3rd May 2016) - Lennon, Mick; Scott, Mark; Collier, Marcus; Foley, Karen
Abstract : Recent years have witnessed a wave of interest in the concept of green infrastructure (GI) as a means of applying an ecosystem approach to spatial planning practice; however, more limited attention has been paid to decision-making processes or tools to enhance GI within spatial plans and guidance. We address this deficit by reporting on the development and application of an interactive group-based methodology to enhance GI 'thinking' and interdisciplinary collaboration, drawing on the literature on the sociology of interactions. Our findings suggest that a game-based approach to GI problem-solving was successful in breaking down professional barriers by creating an informal learning arena, providing an enabling opportunity for participants to solve problems in an iterative, non-linear style to develop principles for action with transferability to ongoing plan formation. This style of problem-solving was characterised by shifting norms and routines of interaction, leading to problem re-framing and a search for alternative solutions.